Guide du Musée Thyssen-Bornemisza. - Llorens, Tomàs; Del Mar Borobia, Maria; Vela, Concha; Museo Thyssen-Bornemisza, Madrid (Madrid : Fundación Colección Thyssen-Bornemisza, 1993)
Bacon, Francis ; Balthus ; Beckmann, Max ; Cézanne, Paul ; Dali, Salvador ; Davis, Stuart ; Degas, Edgar ; Derain, André ; Dix, Otto ; Gauguin, Paul ; van Gogh, Vincent ; Gorky, Arshile ; Gris, Juan ; Grosz, George ; Heckel, Erich ; Hopper, Edward ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Kupka, Frantisek ; Leger, Fernand ; Lichtenstein, Roy ; Lissitzky, El ; Manet, Edouard ; Marc, Franz ; Miro, Joan ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Monet, Claude ; Munch, Edvard ; Nolde, Emil ; Pechstein, Max ; Picasso, Pablo ; Pissarro, Camille ; Pollock, Jackson ; Rauschenberg, Robert ; Renoir, Pierre Auguste ; Rothko, Mark ; Schiele, Egon ; Schmidt-Rottluff, Karl ; Schwitters, Kurt ; de Vlaminck, Maurice
Frans
boek